Sudden onset of syncope and disseminated intravascular coagulation at 14 weeks of pregnancy: a case report - Mayumi Kamata; Tetsuo Maruyama; Tomizo Nishiguchi; Shinya Iwasaki (BMC, 2020)
Abstract Background Amniotic fluid embolism (AFE), also known as anaphylactoid syndrome of pregnancy (ASP), typically occurs during labor and may result in cardiorespiratory collapse and disseminated intravascular coagulation (DIC). There are reports describing less typical presentations of AFE/ASP in which patients do not necessarily have the classic triad of hypoxia, hypotension, and coagulopathy. AFE/ASP rarely occurs in the absence of labor, but such cases may involve medical or surgical abortion, spontaneous miscarriage, or obstetrical procedures including amniocentesis and amnioinfusion. There are, however, no previously reported cases of AFE/ASP with sudden loss of consciousness and disseminated intravascular coagulation occurring during early pregnancy, in the absence of any intervention or obstetric event. Case presentation A 32-year-old G3P2 Japanese woman had sudden-onset syncope at 14 weeks' gestation. On arrival at our hospital, her level of consciousness was severely disturbed as determined by the Glasgow Coma Scale. Although her vital signs were initially stable, blood samples collected intravenously and by femoral artery puncture did not coagulate. A subchorionic hematoma with active extravasation of blood was apparent on contrast-enhanced computed tomography. Two hours after her arrival, she developed hypovolemic shock with progression of DIC, presumably due to intrauterine and retroperitoneal bleeding. After transfusion of blood products; treatments for DIC including the use of recombinant human soluble thrombomodulin, ulinastatin, and corticosteroids; and hysterectomy, her level of consciousness and physical condition improved remarkably. Later investigation of preoperative blood samples revealed that serum levels of AFE/ASP-associated markers were elevated. Immunohistochemical studies on the excised, unruptured uterus showed that amniotic fluid components were present inside a uterine blood vessel. Conclusions This is the first reported patient with sudden-onset syncope and DIC, but without apparent cardiorespiratory collapse, with the highly likely etiology of AFE/ASP occurring at the beginning of the second trimester of pregnancy and in the absence of intervention or delivery. Maternal collapse with DIC during any stage of pregnancy should be considered an AFE/ASP-associated event, even in the absence of labor or obstetric procedures. This event may occur in the presence of subchorionic hematoma alone.